An Evaluation of Human Resource Policies of Moser Baer India Limited - Yadav, Arvind Kumar (Journal of Commerce and Trade, 2015)
Human resource development (HRD) is a subject of great relevance in a developing and most populous country like India. Without these resources, the development of physical/financial/technical resources of the country is not possible. The problems of Human Resource Policies in Moser Baer India Limited at present is also psychological - both the parties mistrusting each other. If the employers begin to treat the workers as equal partners with themselves in production and do not keep the same attitude of aloofness as they do at present, much discontentment among the workers would be removed leading to industrial peace in the country. Too many Labour Laws and much Government interference cannot solve the problem under a democratic set up, rather may irritate the parties. A strong trade union movement, schemes of workers’ co-operation and participation in management, atmosphere of trust and respect on both sides, and implementation of a policy of human relations in industry, will go a long way in the establishment of industrial peace in the country. If India is to achieve world-class productivity levels, labor administration and judicial system has to be made accountable and effectively responsive and efficient. Companies need to focus on creating a positive work culture that optimize respect of rules, dignity and esteem of employees, quality of life and above all accountability and commitment to productivity, quality and cost effectiveness. In this research paper we studied the various human resourse policies of Moser Baer India Limited.